Solutions from character: the author in ancient Homeric criticism - Graziosi, Barbara (2015)
This paper investigates an ancient mode of Homeric interpretation, ‘the solution from character’ (ἡ λύσις ἐκ τοῦ προσώπου). It discusses its ancient intellectual contexts (also in relation to the Aristarchean principle ‘clarify Homer by reference to Homer’, Ὅμηρον ἐξ Ὁμήρου σαφηνίζειν); considers some specific ancient applications; and argues for its usefulness to textual criticism and literary interpretation today. The broader intellectual context of this paper is provided by a research project funded by the European Research Council, and hosted at Durham University: Living Poets: A New Approach to Ancient Poetry, https://livingpoets.dur.ac.uk/.